2021
DOI: 10.21873/anticanres.14924
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Albumin-bilirubin (ALBI) Grade on Non-small Lung Cell Carcinoma: A Propensity-score Matched Analysis

Abstract: Background/Aim: Albumin-bilirubin (ALBI) grade is an indicator of liver dysfunction and is useful for predicting postoperative prognosis of hepatocellular carcinomas. However, the significance of ALBI grade in non-small cell lung carcinoma (NSCLC) has not been elucidated. Patients and Methods: We analyzed 947 patients with pStage IA-IIIA NSCLC. We divided patients into ALBI grade 1 and grade 2/3 groups. We then analyzed the association of ABLI grade with clinicopathological characteristics and prognosis in NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…They showed that the pre-treatment ALBI grade predicted prolonged OS, and that it was superior to the Child–Pugh grade in predicting mortality. In addition, kinoshita et al have compared pre-operative ALBI grade with clinicopathological characteristics and prognosis in patients with resectable non-small cell lung cancer, and reported that ALBI grade 2, 3 was associated with poor prognosis 20 . These previous reports support our results regarding its potential as a suitable biomarker for assessing prognosis in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the pre-treatment ALBI grade predicted prolonged OS, and that it was superior to the Child–Pugh grade in predicting mortality. In addition, kinoshita et al have compared pre-operative ALBI grade with clinicopathological characteristics and prognosis in patients with resectable non-small cell lung cancer, and reported that ALBI grade 2, 3 was associated with poor prognosis 20 . These previous reports support our results regarding its potential as a suitable biomarker for assessing prognosis in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who died had a significantly lower ALBI score than those who survived (2.8±0.4 vs 3.4±0.7, p < 0.001). Patients who died had a significantly lower GCS score (median [Q 1 -Q 3 ]; 8 [3][4][5][6][7][8][9][10][11][12][13] vs 15 [14][15], p < 0.001) but higher ISS (median [Q 1 -Q 3 ]; 33 [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] vs 20 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], p < 0.001) than the surviving patients.…”
Section: Comparison Of Patient and Injury Characteristics In Death An...mentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Patients with cholangiocarcinoma, 28 intrahepatic cholangiocarcinoma, 29 pancreatic cancer with liver metastases, 30 colorectal cancer with liver metastases, 31 and primary biliary cholangitis 32 can all benefit from knowing their ALBI grade as a prognostic indicator. Additionally, other non-hepatological disorders, including aortic dissection, 33 heart failure, 34,35 acute pancreatitis, 36 lung cancer, 24,37,38 esophageal cancer, 39 gastric cancer, 40 lung cancer, 41 and medulloblastoma, 42 have shown a high correlation between ALBI and death.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ALBI has been shown to be prognostic in cancers other than HCC, including pancreatic, colon and gastric cancer, intrahepatic cholangiocarcinoma, extrahepatic bile duct cancer, and even brain cancer (glioma and medulloblastoma). [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] ALBI is likely to be reflective of liver dysfunction in patients undergoing hepatic resection for intrahepatic tumours, such as intrahepatic cholangiocarcinoma or metastatic liver tumours, and tolerance for those undergoing systemic therapy, including chemotherapies, molecular-targeted drugs and immune checkpoint inhibitors. 118 , 123 , [126] , [127] , [128] , 131 , 133 , 134 Although most authors have attempted to link the association of ALBI with a particular cancer to liver function, we should consider whether its association with mortality is actually through some aspect of liver dysfunction or whether it simply reflects the prognostic power of serum albumin and bilirubin levels, independent of liver function.…”
Section: Beyond Liver Diseases – Albi In Non-hepatic Tumoursmentioning
confidence: 99%
“… Kinoshita et al. 132 Retrospective 947 Non-small cell lung cancer ALBI grade 2/3 was an independent predictor of worse cancer-specific survival in patients who underwent resection. Matsukane et al.…”
Section: Beyond Liver Diseases – Albi In Non-hepatic Tumoursmentioning
confidence: 99%